Introducing robotic surgery into an endometrial cancer service–a prospective evaluation of clinical and economic outcomes in a UK institution. Issue 1 (30th March 2015) - Ind, Thomas E. J.; Marshall, Chris; Hacking, Matthew; Harris, Michelle; Bishop, Liz; Barton, Desmond; Bridges, Jane E.; Shepherd, John H.; Nobbenhuis, Marielle
Abstract: Background: We have assessed how the introduction of robotics in a publicly funded endometrial cancer service affects clinical and economic outcomes. Methods: The study included 196 women. Costs were divided into those for wards, high dependency, staffing, theatres, pharmacy, blood products, imaging, pathology and rehabilitation. Capital depreciation was included. Results: Prior to the introduction of robotics, 78/130 (60.0%) cases were performed open, compared to 17/66 (25.8%) afterwards (  p  < 0.0001). The median operative time increased 37 min (95% CI 17–55 min; p  = 0.0002); the median blood loss was 55 ml lower (95% CI 0–150 ml; p = 0.0181); the stay was 2 days shorter (95% CI 1–3; p  < 0.0001). Complications reduced from 64/130 (49.2%) to 19/66 (28.8%) (  p  = 0.0045). Costs reduced from £11 476 to £10 274 (  p  = 0.0065). Conversions for 'straight stick' surgery were 18.2% (14/77) compared to 0.0% (0/24) for robotics (  p  = 0.0164). Conclusions: Introducing robotics resulted in fewer laparotomies, shorter stays, fewer complications and lower costs. © 2015 The Authors. The International Journal of Medical Robotics and Computer Assisted Surgery Published by John Wiley & Sons Ltd.